Legal ambiguities surrounding the role of Regional House of Representatives in Indonesia’s regional autonomy framework - Hariyanto Hariyanto; Muhammad Mutawalli Mukhlis; Muhammad Saleh Tajuddin; Zulhilmi Bin Paidi; Mabarroh Azizah (Legality : Jurnal Ilmiah Hukum, 2025)
Regional autonomy gives local governments the authority to manage their resources, yet there are persistent ambiguities regarding the roles of the Regional House of Representatives (DPRD), which continue to pose governance challenges. The DPRD is intended to act as a legislature at the regional level; however, Law No. 23 of 2014 classifies it as part of the regional government, resulting in overlapping functions with regional heads. The confusion about its role leads to policy inconsistencies, diminished legislative power, and an imbalance favoring the executive branch, thus impairing the effectiveness of regional governance. This study employs a normative legal research method with an analytical approach, supplemented by empirical insights. By examining legal documents, statutory provisions, and practical governance challenges, the research investigates the DPRD’s function within the regional autonomy framework. It identifies key obstacles such as regulatory inconsistencies, limited institutional capacity, and a lack of legislative initiatives. The findings indicate that constraints in human resources and political dependencies further hinder the DPRD’s effectiveness. To address these issues, the study recommends clarifying the legal framework governing the DPRD, enhancing its institutional capacity, and promoting more balanced relationships between the executive and legislative branches. Implementing these measures is vital for achieving more efficient, accountable, and effective regional governance in Indonesia.